2014
DOI: 10.1002/we.1766
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of potential extreme load reduction for a two‐bladed upwind turbine with partial pitch

Abstract: This paper presents a wind turbine concept with an innovative design combining partial pitch with a two-bladed (PP-2B) turbine configuration. Special emphasis is on extreme load reduction during storm situations at standstill, but operational loads are also investigated. In order to compare the loads and dynamics of the PP-2B turbine, a partial pitch three-bladed (PP-3B) turbine and a normal pitch regulated three-bladed (3B) turbine are introduced on the basis of solidity similarity scaling. From the dynamic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Being dismissed for their complex dynamic behavior and unfavorable visual and noise impact since the late 1980s, several innovative two‐bladed turbine designs are currently being tested for the offshore market. Each of these concepts makes use of the characteristic shape of the two‐bladed rotor to address offshore specific challenges, such as accessibility, installation and maintenance . Most recently, the Skywind 3.4 MW prototype has been erected on an onshore site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being dismissed for their complex dynamic behavior and unfavorable visual and noise impact since the late 1980s, several innovative two‐bladed turbine designs are currently being tested for the offshore market. Each of these concepts makes use of the characteristic shape of the two‐bladed rotor to address offshore specific challenges, such as accessibility, installation and maintenance . Most recently, the Skywind 3.4 MW prototype has been erected on an onshore site.…”
Section: Introductionmentioning
confidence: 99%
“…Because two‐bladed turbines are operated at higher tip speed ratios, lower gear ratios and compact transmission components are possible. Furthermore, it was found that two‐bladed turbines possess favorable load behavior in extreme wind conditions . While these properties may imply smaller component dimensions and lower cost, two‐bladed turbines experience higher fatigue loading.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of two-bladed turbines have focused on their aeroservo-elastic control (Solingen, 2015;Solingen et al, 2016a, b;Wang and Wright, 2016) and on their design loads . In the latter study, Kim et al (2015) plots the spectrogram of the tower top signal obtained from nonlinear time simulations of a two-bladed turbine and compares it to the spectrogram of a three-bladed version of the same turbine. There are similarities between these spectrograms which lead the authors to conclude that two-bladed turbines have similar modes as three-bladed turbines.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding time‐variance, it was pointed out by Skjoldan and Hansen as well as Cacciola that due to the rotation of the rotor with respect to a flexible but stationary support structure, every principal eigenmode possesses an infinite number of associated “fan” modes shifted in frequency by ±knormalΩ,kdouble-struckZ. It was shown for two‐bladed turbines by numerical analysis (Hansen and Kim et al) that these fan modes can have a nonneglectable contribution compared with the principal mode. The identification of the principal and the fan modes of time‐variant systems requires the use of periodic analysis methods, such as the implicit Floquet analysis or Hill's method, which can be computationally expensive for high‐fidelity models.…”
Section: Modal Analysismentioning
confidence: 99%